2020
DOI: 10.3340/jkns.2019.0077
|View full text |Cite
|
Sign up to set email alerts
|

Vasa Vasorum Densities in Human Carotid Atherosclerosis Is Associated with Plaque Development and Vulnerability

Abstract: Objective :The extensive vasa vasorum network functions as a conduit for the entry of inflammatory cells or factors that promote the progression of angiogenesis and plaque formation. Therefore, we investigated the correlation between the carotid vasa vasorum activities and carotid plaque vulnerability using indocyanine green video angiography (ICG-VA) during carotid endarterectomy (CEA). Methods : Sixty-nine patients who underwent CEA were enrolled prospectively from September 2015 to December 2017. During CEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…A microchannel on OCT imaging is defined as a non-signal luminal structure image of >3 frames that does not communicate with the lumen ( 19 ). The greater the number of microchannels (≥2), the higher the proportion of TCFAs and the plaques with microchannels are more likely to rupture ( 20 ).…”
Section: Oct Evaluation Of Atherosclerotic Plaque-related Factorsmentioning
confidence: 99%
“…A microchannel on OCT imaging is defined as a non-signal luminal structure image of >3 frames that does not communicate with the lumen ( 19 ). The greater the number of microchannels (≥2), the higher the proportion of TCFAs and the plaques with microchannels are more likely to rupture ( 20 ).…”
Section: Oct Evaluation Of Atherosclerotic Plaque-related Factorsmentioning
confidence: 99%
“…It is thought that several mast cells and their resultant activation affects the stability of plaques. To further understand the role of the vascular network as a transport channel for several angiogenic and plaque forming factors, Joosp et al Used indocyanine green video angiography (ICG-VA) during a carotid endarterectomy (CEA) to investigate the correlation between the change in state of the carotid artery and the vulnerability of a carotid plaque and showed that mast cells stained with CD117 were more frequently found in unstable plaques than in stable ones [68]. Mast cells are activated by the binding and cross-linking of antigens to IgE which is itself bound to the Fcε-receptor (FcεR).…”
Section: Mast Cellsmentioning
confidence: 99%
“…After a few decades, VV has been reported to be closely associated with the development of atherosclerosis by promoting inflammatory processes, resulting in an increase in plaque vulnerability. Therefore, at present, assessing the density of VV has also been considered as a diagnostic indicator [ 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Since VV is very small in diameter and difficult to separate from other tissues in IVUS B-mode images, contrast agents are commonly used to visualize it.…”
Section: Diagnostic Indicators For Atherosclerosismentioning
confidence: 99%
“…Wall shear stress (WSS) indicates the force per lumen area and is calculated as [ 87 , 88 ]: where , , , and are the WSS, absolute viscosity, velocity parallel to the wall, and radial distance from the wall, respectively. The WSS is closely related to the development of atherosclerosis.…”
Section: Diagnostic Indicators For Atherosclerosismentioning
confidence: 99%